Chemotherapy Decision-Making and Survival Outcomes in Older Women With Early Triple-Negative Breast Cancer: Evidence From Real-World Practice - Xiu, Meng; Zhang, Pin; Li, Qing; Yuan, Peng; Wang, Jiayu; Luo, Yang; Ma, Fei; Cai, Ruigang; Fan, Ying; Li, Qiao; Xu, Binghe (Frontiers in Oncology, 2022)
Data regarding chemotherapy options and benefits in older women with early triple-negative breast cancer (TNBC) are limited. Our study aimed to assess the effects of adjuvant chemotherapy on recurrence-free survival (RFS), breast cancer-specific survival (BCSS), and overall survival (OS) rates in elderly TNBC patients. Patients aged ≥65 years diagnosed with stage I-III TNBC (except T1aN0) between 2010 and 2016 were retrospectively included. Multivariate Cox regression was performed to minimize bias. A total of 177 patients were included with a median age of 69 years (range, 65-86), almost all had a Charlson Comorbidity Index of 0-2, and 127 (71.8%) received chemotherapy. Patients who received chemotherapy were younger, had more advanced-stage disease and had better ECOG performance status (P<0.05). Among the 127 patients who were administered chemotherapy, 45 (35%) received taxane plus carboplatin, 36 (28%) received anthracycline-and-taxane-based regimens, and 23 (18%) received taxane-based regimens. The regimen options differed based on patient age and tumour stage (P<0.05). Nearly 80% of the patients completed ≥6 cycles of chemotherapy, and half had their dosage decreased. After adjustment for confounding factors, patients who received ≥6 cycles of chemotherapy were found to have improved RFS rates (hazard ratio [HR], 0.28; 95% confidence interval [CI], 0.09-0.87; P=0.027), and receipt of chemotherapy (≥1 cycle) was associated with better BCSS (HR, 0.19; 95% CI, 0.04-0.97; P=0.046) and OS (HR, 0.26; 95% CI, 0.08-0.87; P=0.029) rates. These results support the considering the risk for recurrence and performing individualized assessments when determining the appropriate chemotherapy approach for older women with early TNBC.